4CPS-391 Non-adherence in rheumatological immune mediated diseases. (14th March 2021) - Rodriguez, A; Carballo, N; Río-No, L; Perez, C; González-Colominas, E; Monfort, J; Grau-Cerrato, S; Ferrández-Quirante, O
Abstract : Background and importance: Patient adherence is a key determinant of treatment success in rheumatological immunomediated diseases. Available data about adherence to biological treatments and factors associated with non-adherence are limited in Spain. Moreover, no studies have compared adherence between subcutaneous and oral drugs. Aim and objectives: To evaluate non-adherence to prescribed subcutaneous biologicals and oral drugs in patients with rheumatological immunomediated diseases and to assess possible predictor factors associated with treatment non-adherence. Material and methods: A retrospective observational study was conducted in all patients receiving oral and subcutaneous treatment for rheumatological immune mediated diseases from 2017 to 2019 in the outpatient pharmaceutical care area of a tertiary university hospital. Non-adherence was evaluated by reviewing all scheduled drug dispensing visits in the computerised application. We considered non-adherent every time that a patient missed at least one drug administration. Data collected were demographic, total patients and patient treatments, total dispensing visits and route of administration for the drug dispensed in every visit. We classified patients as adherent and non-adherent considering the number of dispensing visits. In the non-adherent group, we recorded the number of dispensing visits, reasons for non-adherence, number of missed administrations per patient, and drug and predictor factors for non-adherence. Results: 783 patients were included, aged 52.4 (13.7) years, 427 (54.5%) were women, 164 (20.9%) were smokers and 697 (89%) were Caucasian. 79 (10.1%) of 783 patients received more than one treatment. There were 869 patient treatments: 294 adalimumab (33.8%), 236 etanercept (27.2%), 78 golimumab (8.9%), 47 apremilast (5.4%), 39 certolizumab (4.5%), 34 secukinumab (3.9%) and 30 tocilizumab (3.5%). There were 9197 dispensing visits. Route of administration was 6406 subcutaneous (93.2%) and 374 oral (6.8%). Non-adherence analysis 2417 (26.3%) dispensing visits, reasons for non-adherence/dispensing visits: 92 unjustified (97.5%), 33 infection (1.4%), 18 surgery (0.7%), 3 pregnancy (0.1%), 6 other (0.3%). Number of missed administrations/patient treatments: 675 patients missed at least one administration (77.7%), mean 2.5 (±12.9) missed administrations. Number of missed administrations/drug: 9.9 baricitinib (±20.8), 15.8 tofacitinib (±31.2) and 25.4 apremilast (±53.2). Predictor factors for non-adherence: ethnicity (p=0.015), treatment with golimumab (p=0.006) and tocilizumab (p=0.036) and age (p=0.072). Conclusion and relevance: Non-adherence to the prescribed drug occurred in 77.7% of patients with rheumatological immune mediated diseases. Demographic factors such as ethnicity as well as golimumab and tocilizumab treatment, despite their different frequency of administration, were predictors for non-adherence. Route of administration did not influence non-adherence. References and/or acknowledgements: Conflict of interest: No conflict of interest